Evaluation of Aus Rice (Oryza sativa L.) Production in Less Irrigated Situation in Northern Region of Bangladesh - Sh. Islam, M; Zahid Hossain, ABM; Miah, MS; Shahriar, SM; Mamun, MAA (The Agriculturists, 2017)
Twenty one demonstrations and two validation trials were carried out at the farmers field in the northern region of Bangladesh during 2014 using Aus rice: variety BRRI dhan48 to enhance Aus (pre-monsoon) rice cultivation. Grain yields of 3.5 to 6.5 t ha-1 were obtained from demonstrations plots conducted in different farmers field. The validation trial was conducted in the farmers field at Mithapukur and Nilphamari Sadar Upazillas using BRRI dhan28 and BRRI dhan48 as Braus (rice grown between Boro and Aus season) after harvesting potato. Grain yield of about 5.0 t ha-1 was obtained from the rice variety BRRI dhan28, while 6.6 t ha-1 was obtained from BRRI dhan48. BRRI dhan48, due to its shorter growth duration (100-105 days) required 2-3 less irrigations. About 28-36% less irrigation water was required during dry season when BRRI dhan48 was used as Braus instead of BRRI dhan28 as a Boro crop. About 20 to 60% higher grain yield was observed in different farmers field with BRRI dhan48 over BRRI dhan28, which indicated that BRRI dhan48 is a potential rice variety during Aus or Braus season. BRRI dhan48 can be cultivated after Boro harvest or as Braus after potato harvest. The variety could also decrease the pressure on ground water utilization for rice cultivation during dry season. The Agriculturists 2017; 15(1) 110-115